Credit risk management - Fight, Andrew (Essential capital markets.)
Credit Risk Management will enable general bankers, staff, and credit analyst trainees to understand the basic information and principles underlying credit risk evaluation, and to use those underlying principles to undertake an analysis of non financial and financial risks when preparing a credit proposal. Since the best loans are the ones that do not present problems during the repayment phase, the authors also focus on elements relating to the proactive management of those loans during their inception. This book introduces: *Credit analysis, approval and management processes *Concepts of financial and non-financial risk *Financial statement analysis, including the use of ratio anaylsis *Cash flow analysis and forecasting *Security enhancement & management procedures designed to legally & financially manage credit risk *Inspired by the basic entry level training courses that have been developed by major international banks worldwide. *Will enable students and those already in the finance profession to gain an understanding of the basic information and principles of credit risk *Questions with answers, study topics, practical "real world" examples and text with an extensive bibliography.